Transformasi Pembelajaran pada Jurusan Perhotelan Tingkat SMK di Bali Melalui Aplikasi Simulasi Digital Berbasis Game - I Made Suandana Astika Pande (Bajang Institute, 2026)
Vocational hospitality education in Bali's Sekolah Menengah Kejuruan (SMK) plays a strategic role in supplying skilled labor for the global tourism industry. However, the effectiveness of learning is often hindered by limited physical practice facilities and a lack of interactive teaching methods, creating a gap between students' competencies and industry standards. This study aims to address this problem by developing